Type 2 Diabetes Mellitus Risk Factors Based On An Analytical Epidemiology Approach In Community Health Centers - Ikhsan Ibrahim; Arifina Fahamsya; Farida Fakhrunnisa (International Journal of Health Sciences, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease with increasing prevalence in Indonesia and is a leading cause of morbidity and mortality. According to the 2023 Basic Health Research (Riskesdas), the prevalence of DM in Indonesia has reached 2.3%, with a trend of increasing annually. Community health centers (Puskesmas), as first-level health care facilities, play a crucial role in early detection and control of T2DM risk factors. Objective: This study aims to analyze the risk factors associated with the incidence of Type 2 Diabetes Mellitus based on an analytical epidemiological approach in the working area of Health Center X. Methods: The study design used a case-control study approach with a sample size of 100 respondents (50 cases and 50 controls). Independent variables included age, obesity, physical activity, diet, family history, and smoking habits. Data analysis was performed bivariately using the Chi- Square test and multivariately using multiple logistic regression. Bivariate analysis showed that variables significantly associated with the incidence of Type 2 DM were obesity (p = 0.001), low physical activity (p = 0.003), high-calorie diet (p = 0.002), and family history of DM (p = 0.004). Logistic regression results showed that obesity was the most dominant risk factor with Odds Ratio (OR) = 5.6 (95% CI: 2.1–14.9). Conclusion: Obesity, low physical activity, high-calorie diet, and family history of DM have been shown to be significant risk factors for the occurrence of Type 2 Diabetes Mellitus. Preventive efforts can be carried out through balanced nutrition education, promotion of physical activity, and early detection in individuals with high-risk factors.